A novel nanoformulation of PLGA with high non-ionic surfactant content improves in vitro and in vivo PTX activity against lung cancer. (March 2019) - Jiménez-López, Julia; El-Hammadi, Mazen M.; Ortiz, Raul; Cayero-Otero, Maria D.; Cabeza, Laura; Perazzoli, Gloria; Martin-Banderas, Lucia; Baeyens, Jose M.; Prados, Jose; Melguizo, Consolación
Graphical abstract: Abstract: Paclitaxel (PTX), a chemotherapy agent widely used to treat lung cancer, is characterised by high toxicity, low bioavailability and the need to use of excipients with serious side effects that limit its use. Paclitaxel encapsulation into nanoparticles (NPs) generates drug pharmacokinetic and pharmacodynamic advantages compared to free PTX. In this context, a NP carrier formed from a copolymer of lactic acid and glycolic acid (PLGA) has demonstrated high biocompatibility and low toxicity and therefore being approved by FDA to be used in humans. We synthesised a new PLGA NP and loaded it with PTX to improve drug efficacy and reduce side effects. This nanoformulation showed biocompatibility and no toxicity to human immune system. These NPs favor the intracellular uptake of PTX and enhance its antitumor effect in human and murine lung cancer cells, with up to 3.6-fold reductions in the PTX's IC50 . Although PLGA NPs did not show any inhibitory capacity against P-glycoprotein, they increased the antitumor activity of PTX in cancer stem cells. Treatment with PLGA-PTX NPs increased apoptosis and significantly reduced the volume of the tumorspheres derived from A549 and LL2 cells by up to 36% and 46.5%, respectively. Biodistribution studies with PLGA-PTX NPs revealed an increase in drug circulation time, as well as a greater accumulation in lung and brain tissues compared to free PTX. Low levels of PTX were detected in the dorsal root ganglion with PLGA-PTX NPs, which could exert a protective effect against peripheral neuropathy. In vivo treatment with PLGA-PTX NPs showed a greater decrease in tumor volume (44.6%) in immunocompetent mice compared to free PTX (24.4%) and without increasing the toxicity of the drug. These promising results suggest that developed nanosystem provide a potential strategy for improving the chemotherapeutic effect and reducing the side effects of PTX.